2017
DOI: 10.1155/2017/3649397
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Complications following Blood Transfusions in Sickle Cell Anemia

Abstract: In Sickle Cell Anemia (SCA) patient blood transfusions are an important part of treatment for stroke and its prevention. However, blood transfusions can also lead to complications such as Reversible Posterior Leukoencephalopathy Syndrome (RPLS). This brief report highlights two cases of SCA who developed such neurological complications after a blood transfusion. RLPS should be considered as the cause of neurologic finding in patients with SCA and hypertension following a blood transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…Case reports of patients with sickle cell anaemia (SCA; HbSS and HbSβ 0 genotypes) who developed complications after RBC transfusions have contributed to recommendations for avoiding Hb increases beyond 100 g/l. Patients in these reports developed adverse neurological outcomes, ranging from headaches to seizures and fatal cerebral bleeds, within days of receiving RBC transfusions 7–11 . As such, the rate of Hb increase, in addition to the final Hb value, may be an important factor that engenders complications, e.g.…”
Section: The Rationale Behind the Haemoglobin 100 G/l Limit With Red Blood Cell Transfusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Case reports of patients with sickle cell anaemia (SCA; HbSS and HbSβ 0 genotypes) who developed complications after RBC transfusions have contributed to recommendations for avoiding Hb increases beyond 100 g/l. Patients in these reports developed adverse neurological outcomes, ranging from headaches to seizures and fatal cerebral bleeds, within days of receiving RBC transfusions 7–11 . As such, the rate of Hb increase, in addition to the final Hb value, may be an important factor that engenders complications, e.g.…”
Section: The Rationale Behind the Haemoglobin 100 G/l Limit With Red Blood Cell Transfusionmentioning
confidence: 99%
“…Circulating free haem, resulting from chronic haemolysis, reduces nitric oxide bioavailability and restricts vasodilation 14,15 . An acute rise in blood pressure has been noted in case reports of patients who received several RBC transfusions before developing neurological complications 7–11 . Given the underlying vascular dysfunction, the microvasculature may be unable to compensate for this rapid change in blood volume and Hb level.…”
Section: The Effect Of Viscosity On Blood Flow In Sickle Cell Diseasementioning
confidence: 99%
“…Those microhemorrhages could contribute to neurological conditions that these subjects might suffer from [69]. In fact, this is supported by a study with children affected by hemoglobinopathies [70], and developing a reversible neurological complication, known as leukoencephalopathy syndrome, upon blood transfusion [71]. This means that blood treatments might cause long-term effects to organs such as the brain, which might result from potential iron accumulation over time.…”
Section: The Cytotoxicity Of Iron In the Brainmentioning
confidence: 99%
“…It should be noted that although complications of blood transfusion are rare, it can be life threatening because massive blood transfusions can result in abnormalities of coagulation status, vascular permeability, acid-base balance and temperature hemostasis 31 . Previous studies have demonstrated that the large quantity of blood transfusions can cause complications such as reversible posterior leukoencephalopathy syndrome [32][33][34] . Furthermore, blood transfusion may cause a rapid increase in total blood volume, which further leads to cerebral blood flow overload.…”
Section: Surgical Outcome Of Ich With Prior Antithrombotic Treatmentmentioning
confidence: 99%
“…Furthermore, blood transfusion may cause a rapid increase in total blood volume, which further leads to cerebral blood flow overload. It has been suggested that an abrupt or acute cerebral hyperperfusion exceeding the capacity of autoregulation of cerebral capillary perfusion pressure could result in vasogenic edema 34 .…”
Section: Surgical Outcome Of Ich With Prior Antithrombotic Treatmentmentioning
confidence: 99%